Perlindungan Hukum terhadap Pekerja Alih Daya dalam Perjanjian Kerja dalam Hal Terjadi Peralihan Perusahaan Penyedia Jasa - Fitri, Idul; Khairani, Khairani; Yasniwati, Yasniwati (Faculty of Law, Andalas University, 2024)
Outsourced labor is a part of employment growth in various economic sectors. As part of the workforce, outsourcing workers must also receive protection for their rights as outsourcing workers. One of the things that needs to be protected is in the event of a transfer of service provider company. Therefore, it is necessary to study the protection of the rights of outsourced workers. In this case, the research was conducted at the M. Zein Painan Hospital. Outsourced workers at M. Zein Painan Hospital must be protected by Indonesian law. The study used empirical research methods by collecting data from related parties, namely outsourcing workers, service provider companies, and service users, in this case, Dr. M Zein Painan. One form of legal protection and certainty, especially for workers, is through the implementation of work agreements. Analysis and discussion of the results obtained are: (a) Forms of legal protection for outsourced workers in work agreements at RSUDi Dr. M. Zein Painan, namely protection of wages, protection of working time, and protection of rest time as well as protection against termination of employment (b) Implementation of work agreements for outsourced workers when there is a change in service provider company can be implemented well with the existence of an agreement Work.